Spontaneous Rupture of an Unscarred Uterus Caused by Near-Cornual Pregnancy with Placenta Accreta at 4 Months of Pregnancy - Wen-Chu Huang; Fang-Yu Hung; Chih-Ping Chen; Chen-Ju Lin (Elsevier, 2005)
Objective: We present a case of spontaneous uterine rupture caused by near-cornual pregnancy with placenta accreta and emphasize the possibility of uterine rupture at all stages of pregnancy. Case Report: A 32-year-old woman, gravida 3, para 2, was referred at 16 weeks of gestation under the condition of death on arrival. Uterine rupture with massive internal bleeding was diagnosed. Emergency hysterectomy was performed. There was a sagittal perforating arc near the right cornu from the anterior to the posterior surface over the dome of the uterus. The final histopathologic examination indicated a near-cornual pregnancy with placenta accreta. Complications of massive hemorrhage occurred, and the patient expired due to multiple organ failure. Conclusions: Spontaneous rupture of an unscarred uterus can occur at any stage of pregnancy. The placental implantation near the cornu with accreta may have been the cause of the uterine rupture in this patient. Noting the site of implantation should be an important component during antenatal sonography. Furthermore, uterine rupture should be included in the differential diagnosis of pregnant women with abdominal pain.